Assistance with Visualization Publication on Jasdam II/Sriwijaya Instagram - Pratama, Ahmad Fauzi; Maharani, Dwi; Misnawati, Desy; Siti Rahayu Pratami Lexaningrum (Jurnal Pengabdian Pancasila (JPP), 2023)
Visual communication design is one application for creating a good image for Jasdam II Sriwijaya, the concept of communication and expression of creative power, which is applied in various visual communication media by processing graphic design elements consisting of images (illustrations), letters, colors, composition and layout. All of this is done to convey messages visually, audio and audio-visually to the intended targets. Instagram media is an alternative media for publishing information on activities at Jasdam II Sriwijaya. The aim of community service activities is to provide assistance. The community service method is through mentoring through 1) preparation, 2) implementation and 3) evaluation. The result of community service activities is that there is an increase in visits to Jasdam II/Sriwijaya due to seeing Jasdam II/Sriwijaya Instagram posts and Instagram story followers, likers and viewers also increase. After carrying out this community service activity, the community service team had a positive impact in introducing the Jasdam II/Sriwijaya environment to the community.